Spectrum of Surgically Treated Congenital Heart Diseases: Single Center Experience (Medical Forum Monthly, 2021)
Objective: Congenital heart disease is the most common birth defect. Congenital heart disease was the underlying cause of an estimated 261 247 deaths globally in 2017. Childrens hospital Lahore is one of the top three high volume center in Pakistan, where more than 1000 cases of congenital heart disease are surgically treated. In this article author has discussed spectrum of diseases which are being treated surgically at Children’s Hospital Lahore.Study Design: A Retrospective StudyPlace and Duration of Study: This study was conducted at the Children’s Hospital/Institute of Child Health Lahore from January, 2019 to December, 2019.Materials and Methods: Depending on diagnosis of condition and co morbid status a combined decision between pediatric cardiologists and surgeons was made regarding choice of intervention in the cath conference after reviewing the echocardiogram, angiogram, CT, pulse oxymetry etc.Results: 1177 patients underwent cardiac surgeries. 402 (34%) underwent closed heart surgeries. 61% were male. Age group 1 month to 12 months was the most common age group that made 34% of all cases., TOF, VSD and PDA made the bulk of cases.Conclusion: Most of the congenital heart diseases can be managed surgically at our institute. With the rising incidence of CHD in Asian countries such as Pakistan, establishment of pediatric cardiac surgery units have allowed for the provision of quality care. VSD closure, TOF repair and PDA ligation were the most commonly performed surgical procedures.